2017
DOI: 10.1002/sctm.16-0415
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Mesenchymal Stromal Cell-Based Approaches for the Treatment of Acute Respiratory Distress and Sepsis Syndromes

Abstract: Despite extensive research on candidate pharmacological treatments and a significant and increasing prevalence, sepsis syndrome, and acute respiratory distress syndrome (ARDS) remain areas of unmet clinical need. Preclinical studies examining mesenchymal stromal cell (MSCs) based‐therapies have provided compelling evidence of potential benefit; however, the precise mechanism by which MSCs exert a therapeutic influence, and whether MSC application is efficacious in humans, remains unknown. Detailed evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 99 publications
(121 reference statements)
1
59
0
3
Order By: Relevance
“…Ample preclinical evidence indicates that MSCs can be an effective adjunctive therapy in patients with sepsis or noninfectious critical illness . A recent meta‐analysis including 20 controlled experiments in preclinical sepsis models reported that treatment with MSCs reduced the odds of mortality of experimental sepsis by approximately 73% over a range of investigational conditions .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ample preclinical evidence indicates that MSCs can be an effective adjunctive therapy in patients with sepsis or noninfectious critical illness . A recent meta‐analysis including 20 controlled experiments in preclinical sepsis models reported that treatment with MSCs reduced the odds of mortality of experimental sepsis by approximately 73% over a range of investigational conditions .…”
Section: Discussionmentioning
confidence: 99%
“…At a high dose (4 × 10 6 cells/kg), ASCs had clear signs of biological activity, exerting a variety of proinflammatory, anti‐inflammatory, and procoagulant effects during human endotoxemia. Notably, while many previous studies examined the effect of MSCs in inflammation and sepsis models in animals , this investigation is the first to study the effect of MSCs on inflammatory responses in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson et al stated that cell therapy was commonly performed before or at the time of infection in the designed models to evaluate the effect of stem/stromal cells on damage and this is not suitable for most septic patients [75]. The results also show that the experimental model of the acute pulmonary inflammation peaks after infusion of infectious agents at 24-48 h. Accordingly, in a study by Mokhber Dezfouli et al, transplantation of stem/stromal cell was performed 24 h after inflammation with maximal inflammatory symptoms, in contrast to most of the studies that have performed stem/stromal cell transplantation between 30 min and 4 h after inflammation.…”
Section: Msc Therapy In the Model Of Pulmonary Diseasesmentioning
confidence: 99%